Effect of using songs to teach junior secondary mathematics - Abisola.O., Lawani; Abayomi.A, Arigbabu; Adetayo, Janet Oyebola (Journal of Education in Black Sea Region, 2022)
Singing songs is part of human everyday lifestyle, they can easily be recalled and thereafter affect other aspects of human life. The study examined the effect of songs application in teaching junior secondary mathematics. The junior secondary level being the intermediate and upper basic level of education where learners are prepared for the serious academic rigour of the post-basic or senior secondary level in Nigeria require the introduction of more learner-centred, learner-friendly and activity-based methods. Teaching Mathematics with use of songs will be one of such methods. The study employed the pre- test, post-test, quasi experimental design. Using purposive sampling technique, one hundred and twenty (120) junior secondary students from two public secondary schools were selected for the sample. Three hypotheses were formulated and tested. Two instruments, procedural and main instrument, were used. The data collected were analyzed using analysis of covariance (ANCOVA). The result of the study revealed that there was a significant effect of songs on the academic achievement of students in Mathematics and it was recommended that teachers should be encouraged to adopt songs composed during teaching since their use sustains students’ interest and retention.